Nietzsche and the ancient skeptical tradition - Berry, Jessica N. (New York ; Oxford : Oxford University Press, 2011)
This work presents a portrait of Nietzsche as the skeptic par excellence in the modern period, by demonstrating how a careful and informed understanding of ancient Pyrrhonism illuminates his reflections on truth, knowledge and morality, as well as the very nature and value of philosophic inquiry.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 12, 2011).
Keywords: Nietzsche, Friedrich Wilhelm, -- 1844-1900.; Skeptics (Greek philosophy); Skepticism